Combination of Fingerprint and Hidden Load Cell (CFH) - Hashim, Mohamad Ridzuan Bin; Ya Abdullah, Norhaiza (Journal of Computing Technologies and Creative Content, 2017)
The aim of this project is to improve the implemented security policy in the use of fingerprint readers in areas with important data by combining applications system and hardware. In order to ensure safety can be enhanced using a fingerprint reader combined load cell where the user is allowed to enter certain areas should identify where is the load cell is placed or hidden areas. If the use is authorized to access the area they would be able to identify where the load cell is placed. The pressure shall exceed the limit set by the system to allow the fingerprint reader responded by giving the user permission to process fingerprints. Among the advantages of using this system is not able to identify the intruder why fingerprint reader does not work. In addition, the use of load cells placed on an area that cannot be seen with the naked eye, for example in the wall or floor. Next combination of fingerprint and hidden load cell system can save lot of money for organization from buying other surveillances system to ensure the safety of their data secure.